Pilot Study on the Current Management of Children with COVID-19 In Hospitals in Bangladesh; Findings and Implications - Nusrat, Nadia; Haque, Mainul; Chowdhury, Kona; Adnan, Nihad; Lutfor, Afzalunnessa Binte; Karim, Enamul; Hassan, Mahmuda; Rabbany, Arif; Begum, Dilara; Hasan, Mohammad Nazmul; et al. (Bangladesh Journal of Medical Science, 2021)
Objective: The focus on COVID-19 in children in low- and middle-income countries including Bangladesh has been on addressing key issues including poor vaccination rates as well as mental health issues, domestic violence and child labour. However, the focus on optimally managing children in hospitals is changing with new variants and concerns with the development of hyperinflammatory syndromes. There are also concerns with the overuse of antimicrobials to treat patients with COVID-19 in hospitals enhancing resistance rates. The Bangladesh Paediatric Association have developed guidelines to improve patient care building on national guidance. Consequently, there is a need to document the current management of children with COVID-19 in Bangladesh and use the findings for future guidance. Methods: Rapid analysis of the management of children with COVID-19 among eight private and public hospitals in Bangladesh with varying numbers of in-patient beds using purposely developed case report forms (CRFs). The CRFs were piloted before full roll-out. Results: Overall low numbers of children in hospital with COVID-19 (4.3% of in-patient beds). The majority were male (59.6%) and aged 5 years or under (63.5%). Reasons for admission included respiratory distress/ breathing difficulties with 94.2% of COVID-19 cases confirmed. All children were prescribed antibiotics empirically, typically those on the Watch list of antibiotics and administered parenterally, with only a small minority switched to oral therapy before discharge. There was appreciable prescribing of Vitamins (C and D) and zinc and encouragingly limited prescribing of other antimicrobials (antivirals, antimalarials and antiparasitic medicines). Length of stay was typically 5 to 10 days. Conclusion: Encouraging to see low hospitalisation rates and limited use of antimicrobials apart from antibiotics. Concerns with high empiric use of antibiotics and limited switching to oral formulations can be addressed by instigating antimicrobial stewardship programmes. We will be monitoring this. Bangladesh Journal of Medical Science Vol.20(5) 2021 p.188-198